2021
DOI: 10.3390/en14020465
|View full text |Cite
|
Sign up to set email alerts
|

GHG Emissions Mitigation in the European Union Based on Labor Market Changes

Abstract: The effects of the labor market on environmental issues are an actual problem at the global level, and recommendations are required to achieve equilibrium between labor productivity and environmental protection. Considering the ecological limits of work and the necessity of reducing the working time to mitigate GHG (greenhouse gas) emissions, this paper aims to assess the impact of the labor market on GHG emissions in the EU-28 countries. Using panel data models for 2007–2019, a positive effect of working time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…Compared to developed countries, in the CEE states, the effect of labor productivity on pollution is explained by the low technological progress in industry. The study by Simionescu et al (2021) for all the EU countries supported the hypothesis that labor productivity should be reduced to achieve sustainable development in the long term.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Compared to developed countries, in the CEE states, the effect of labor productivity on pollution is explained by the low technological progress in industry. The study by Simionescu et al (2021) for all the EU countries supported the hypothesis that labor productivity should be reduced to achieve sustainable development in the long term.…”
Section: Discussionmentioning
confidence: 62%
“…Simionescu et al (2021) have indicated the positive effect of labor productivity on GHG emissions in EU-28 countries between 2007 and 2019. The same influence was observed in the US in the period spanning 2007 to 2013 and working time reduction is recommended for emissions mitigation.❖ Indicators showing the quality of governance.…”
mentioning
confidence: 99%
“…The first international "degrowth conference" was held in 2008 in Paris. The methodological appeal of this framework is that it can be applied to any rural area as well as it is highly independent (Huylenbroek et al, 2007;Chaskin, 2008;Wilson, 2010;Kovách, 2012;Alabán, 2013, Simionescu et al, 2021.…”
Section: Fig 2 Multifunctional Quality -Intersection Of Economic Social and Environmental Capitalmentioning
confidence: 99%
“…One of the priorities for researchers, designers, and operators of energy systems is the development and effective deployment of clean energy technologies on an industrial scale. This is motivated, in part, by the need to reduce greenhouse gas emissions, which would directly mitigate the fast-progressing climate change [ 1 , 2 ]. Attempts to deploy biofuel production systems on an industrial scale have shown that such technologies are complex process-wise, difficult to maintain, and require high investment costs [ 3 ].…”
Section: Introductionmentioning
confidence: 99%